THE POSSIBILITY OF TEACHING PRACTICES AS A COMMUNITY OF PRACTICE BASED UPON THE EXPERIENCES OF STUDENT-TEACHERS - Blaszk, Martin (Neofilolog, 2020)
In pre-service training for teachers of English opportunities for dialogic interaction (Skidmore and Murakami, 2017) with a mentor are seen to play an important role in professional awareness and development (Wallace, 1993; Gabryś-Barker, 2012; Howard and Donaghue, 2015). To fulfil the demands of their practices student-teachers work with a number of different people: a school teacher (mentor), academic supervisor and the academic staff who lead the English teaching methodology course (Blaszk, 2015). This being the case, it was hypothesized that teaching practices might exist as a community of practice within which student-teachers in interaction with these different people would be supported in their professional development. The aim of the qualitative research reported in this paper was to discover how the student-teachers in a particular institution perceived their teaching practices and whether or not those practices could be viewed as a community of practice that supported the students.